2021
DOI: 10.3390/cancers13184657
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design of a Novel Nozzle Combined with a Clinical Proton Linac for Magnetically Focussed Minibeams

Abstract: (1) Background: Proton minibeam radiation therapy (pMBRT) is a novel therapeutic approach with the potential to significantly increase normal tissue sparing while providing tumour control equivalent or superior to standard proton therapy. For reasons of efficiency, flexibility and minibeam quality, the optimal implementation of pMBRT should use magnetically focussed minibeams which, however, could not yet be generated in a clinical environment. In this study, we evaluated our recently proposed minibeam nozzle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…It might be the time to abandon the old paradigm in RT and embrace new modalities using radically different ways of depositing the dose, such as SFRT and FLASH therapy, and even in the future the combination of both (Ref. 92). The lesson being taught by SFRT and FLASH therapy is that the exploration of the vast 'terra incognita' on how the physical parameters of the irradiation modify the biological response can offer enormous opportunities for optimal patient treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be the time to abandon the old paradigm in RT and embrace new modalities using radically different ways of depositing the dose, such as SFRT and FLASH therapy, and even in the future the combination of both (Ref. 92). The lesson being taught by SFRT and FLASH therapy is that the exploration of the vast 'terra incognita' on how the physical parameters of the irradiation modify the biological response can offer enormous opportunities for optimal patient treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The latter approach removes the need for any mechanical collimation, which improves irradiation efficiency and flexibility as well as the degree of spatial fractionation in healthy tissue. Moreover, a recent conceptual design study has showed that this new minibeam nozzle in combination with proton LINAC accelerators such as LIGHT (Advanced Radiotherapy Plc) may provide an optimal implementation of pMBRT by allowing the generation of magnetically focussed minibeams with clinically relevant parameters (Ref 92)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study was carried out considering the pencil beam dimensions of an existing clinical machine, in the presence of a static collimator. Further studies should also investigate these approaches in the case of irradiation with magnetically focused minibeams, which could be even smaller and obtained without a mechanical collimator [ 28 , 29 ]. It is worth observing that minibeam width is not significantly affected by dipole magnetic fields, except when a dipole is coupled with a static multislit collimator ( Configuration #2 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, magnetic fields can be used to intentionally deflect or focus particle beams around the treatment isocenter: this approach has been proposed by [ 27 ], who demonstrated the feasibility of converging 160 MeV VHEE beams using external magnetic fields and two electromagnetic quadrupole triplets, or by [ 28 , 29 ], who proposed a new technique for generating a proton minibeam through magnetic focusing in an optimized nozzle design.…”
Section: Introductionmentioning
confidence: 99%